Elite adolescent athletes' use of dietary supplements: characteristics, opinions, and sources of supply and information - Diehl, Katharina; Schneider, Sven; Thiel, Ansgar; Zipfel, Stephan; Mayer, Jochen; Schnell, Alexia (International journal of sport nutrition and exercise metabolism, 2012)
The authors' aim was to examine the prevalence of (daily) dietary-supplement (DS) use among elite adolescent athletes and to differentiate use by different types of DS according to their function. Data were analyzed for associations between users of these DS types, sociodemographic, sport-specific characteristics, and opinion on the need for DS. In addition, sources of supply and information were examined. In the framework of the GOAL Study, 1,138 German elite adolescent athletes (14-18 yr) answered questions about DS. The data were analyzed to identify groups at risk for using DS after a classification by supplemental function. Of the young athletes, 91.1% reported DS use during the previous month. (Daily) DS use was significantly associated with sex, kind of sport, and the weekly duration of sporting activity. Furthermore, some athletes were required to use DS by their sporting organization. DS use was more likely in these athletes than in those whose sporting organizations had no such requirement. Overall, DS with short- and long-term supplemental function were mostly associated with the use of magnesium. However, DS with medium-term muscle-building function played an important role among daily users. The main source of information about DS was coaches; main source of supply was parents. Professional education is urgently needed, as 9 out of 10 athletes used DS, and strong positive opinions toward the use of DS were present, particularly in the DS users.